(untitled) (Research, Society and Development, 2020)
The present work has as a reflexive analysis based on the literature on the association of early stress and the development of depression. The method is a descriptive study, of the type reflexive analysis, with the discussion of the literature from three categories: early stress, depression, and influences of early stress in adult depression. As a result, early stress experiments influence neurobiological systems, within genetic limits, leading to behavioral manifestations of depression. It is these childhood adverse experiences that contribute significantly to the pathophysiology of depression. The role of stress in the disequilibrium of the health-disease process is related to multifactorial causes. However, knowing what happens between stress in its primary form, early stress, and mental illness development, especially depression, is essential for directing mental health care practices at the interventional and preventive measures. Further studies in the area are needed, especially those related to neurobiological aspects.